6(r-6)=-66

Simple and best practice solution for 6(r-6)=-66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(r-6)=-66 equation:


Simplifying
6(r + -6) = -66

Reorder the terms:
6(-6 + r) = -66
(-6 * 6 + r * 6) = -66
(-36 + 6r) = -66

Solving
-36 + 6r = -66

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 6r = -66 + 36

Combine like terms: -36 + 36 = 0
0 + 6r = -66 + 36
6r = -66 + 36

Combine like terms: -66 + 36 = -30
6r = -30

Divide each side by '6'.
r = -5

Simplifying
r = -5

See similar equations:

| 8x(2n+3x)=10 | | 21n^2+14n+7=6n+11 | | -(4-5z)-2(-3z+4)-3z=-2(6-4z-8(1-z)) | | 5(3-5n)=65 | | 21n^2+8-4=6n+11 | | 5+6-3x=-4 | | 5a-10b=45 | | 4x+89=6x+109 | | 21n^2+8-4= | | 15-2y=15+3y | | X^2-2ax=6ab-3bx | | 5(s-1)=94-2(s-4) | | 4x-5+6=45 | | 20x=280 | | x^3-31x-30=0 | | 3a+b=54 | | -3(2y-4)-6= | | (5p-3p)=2p+9 | | 16x-13=7x+32 | | 2z^2+19-10=0 | | 4.9=4t+(-7t) | | -24=-4y-8 | | 18x-13=6x+47 | | 2x+(y^2)+2=0 | | -9x-4y=-1 | | -14x-4=-13x+6 | | 2w+2(2w+1)=36 | | 1.6y+12y=0 | | 18x+12=12x+6 | | 1.2x-9=-11 | | -15x-3=-10x-18 | | 2x+4-2x+2=3 |

Equations solver categories